Eating out : social differentiation, consumption, and pleasure - Warde, Alan (Cambridge University Press, 2000)
Eating Out is a fascinating study of the consumption of food outside the home. Through recent in-depth research in English cities, the authors have collected a wealth of information into people's attitudes towards, and expectations of, eating out as a form of entertainment and an expression of taste and status.